2010
DOI: 10.1159/000322905
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reduction by Ivabradine Reduces Diastolic Dysfunction and Cardiac Fibrosis

Abstract: Objectives: To determine if heart rate (HR) reduction with ivabradine (IVA), a selective inhibitor of the pacemaker If current, prevents cardiac dysfunction associated with dyslipidemia. Methods: New Zealand White rabbits received either a standard diet, a 0.5% cholesterol-enriched diet only (CD), or a 0.5% CD with IVA (17 mg/kg/day) for 12 weeks. HR, left ventricular (LV) systolic function, diastolic function and LV regional myocardial performance index (MPI) were studied using echocardiography. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 59 publications
7
35
0
1
Order By: Relevance
“…33 Recently, it was reported that HR reduction by ivabradine was able to reduce diastolic dysfunction and cardiac fibrosis in an experimental model of hypercholesterolemia. 34 It has been shown that ivabradine increases diastolic time 35 and enhanced ventricular relaxation during peak exercise 36 to a greater extent than ␤-blockers, which is in agreement with our findings. In contrast to ␤-blockers, ivabradine did not decrease the maximal rise in LV pressure with time (dP/dt max ) or alter postsystolic wall thickening.…”
Section: Discussionsupporting
confidence: 93%
“…33 Recently, it was reported that HR reduction by ivabradine was able to reduce diastolic dysfunction and cardiac fibrosis in an experimental model of hypercholesterolemia. 34 It has been shown that ivabradine increases diastolic time 35 and enhanced ventricular relaxation during peak exercise 36 to a greater extent than ␤-blockers, which is in agreement with our findings. In contrast to ␤-blockers, ivabradine did not decrease the maximal rise in LV pressure with time (dP/dt max ) or alter postsystolic wall thickening.…”
Section: Discussionsupporting
confidence: 93%
“…Circulating angiotensin II levels were significantly lowered by ivabradine and correlated with HR. Aldosterone levels also correlated with HR during treatment and were lower with ivabradine [16]. Results in experimental studies are consistent with the effects of ivabradine on cardiac remodeling [11].…”
Section: Discussionsupporting
confidence: 76%
“…Busseuil et al [16] demonstrated that selective HR reduction with ivabradine prevented the detrimental effects of hypercholesterolemia on LV myocardial performance. Ivabradine attenuated LV diastolic dysfunction, reduced left atrial and LV structural remodeling (interstitial fibrosis), and reduced LV collagen type I in hypercholesterolemic rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This use is supported in recent literature due to its heart rate lowering effect. [14][15][16] Ivabradine has a beneficial effect in DCM especially in those who have heart rates not controlled with beta blockers. In few patients due to the heart rate lowering effect of beta blockers, syncope occurred and in those cases Digoxin was used as an alternative.…”
Section: Discussionmentioning
confidence: 99%